Adult pancreatoblastoma with atypical histological morphology combined with familial adenomatous polyposis: a rare case report - Wang, Ying-Xia; Fan, Su-Su; Peng, Xue-Rong; Zhu, Yu-Shan; Zhang, Xuan (Frontiers in Oncology, 2024)
Pancreatoblastoma(PB) is a rare malignant pancreatic epithelial tumor that mostly occurs in children and occasionally occurs in adults. The tumor has acinar cell differentiation and squamous corpuscles/squamous epithelial islands, which are frequently separated by fibrous bundles. Familial adenomatous polyposis (FAP) is an autosomal dominant inherited disease characterized by the presence of numerous adenomatous polyps in the colon and rectum.Cases of pancreatoblastoma combined with familial adenomatous polyposis (FAP) are rarely reported. A review of a rare case of adult pancreatoblastoma with atypical histological morphology combined with familial adenomatous polyposis is presented herein. In this case, the patient was first diagnosed with familial adenomatous polyposis and subsequently found to have pancreatoblastoma 1 year and 3 months later. This suggests pancreatoblastoma may occur in patients with familial adenomatous polyposis or a family history of the condition, indicating a possible association between the two tumors. Therefore, pancreatoblastoma should be included in a differential diagnosis for FAP patients with a pancreatic mass. This case report also can improve the awareness of clinicians, radiologists, and pathologists on the presence of the rare tumor-adult pancreatoblastoma in patients with familial adenomatous polyposis.